Self-Injurious Behaviour in SCA17: A New Clinical Observation. (5th September 2019) - Bonomo, Roberta; Latorre, Anna; Bhatia, Kailash P
Background: Self-injurious behaviour has historically been associated with borderline personality disorder. Nevertheless, over recent years, it has been reported in numerous neurological syndromes, especially hyperkinesias. Case report: Two cases of SCA17 manifested self-injurious behaviour, namely repetitive scratching of the skin resulting in severe excoriations. In one of them, the abnormal behaviour was associated with the inability to resist the impulse to commit the act along with relief following the damage. Discussion: This is the first report describing self-injurious behaviour in SCA17, but the mechanisms underlying it are still not clear. Further studies are needed to clarify the pathophysiology of such manifestation in hyperkinetic syndromes.